2009
DOI: 10.1088/0963-0252/18/4/045020
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of coupling oscillation in Hall thrusters

Abstract: The characterization of coupling oscillation in a Hall thruster is experimentally studied by varying magnetic flux density or discharge voltage to obtain the relationship between discharge parameters and coupling oscillation. The dispersion relation of coupling oscillation is deduced using a 2D collisionless quasi-neutral fluid model and the factors having their effects on coupling oscillation are obtained. Experimental results and theoretical analysis indicate that coupling oscillation increases with magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…It is seen from the figure that the instability grows faster in the presence of stronger magnetic field. Wei et al [23] also observed experimentally an enhancement in the growth rate of coupling instability with the magnetic field. The large growth rate is attributed Since the presence of at least one point of inflection in the velocity profile is required for the Rayleigh instability, it is plausible that the nonuniformity in the velocity is enhanced in the presence of the magnetic field due to the electrons' gyratory motion and that the instability grows at a faster rate.…”
Section: Results Of Growth Rate and Perturbed Potentialmentioning
confidence: 89%
See 1 more Smart Citation
“…It is seen from the figure that the instability grows faster in the presence of stronger magnetic field. Wei et al [23] also observed experimentally an enhancement in the growth rate of coupling instability with the magnetic field. The large growth rate is attributed Since the presence of at least one point of inflection in the velocity profile is required for the Rayleigh instability, it is plausible that the nonuniformity in the velocity is enhanced in the presence of the magnetic field due to the electrons' gyratory motion and that the instability grows at a faster rate.…”
Section: Results Of Growth Rate and Perturbed Potentialmentioning
confidence: 89%
“…Hence, a broader frequency band is realized in a more realistic situation where the plasma species carry finite temperature. This interesting frequency band was not explored by other investigators [6][7][8][12][13][14][15][16]23,25] and is the new result. Based on this, the oscillations (perturbations) of only higher frequency would grow into instability if the plasma contains stronger density gradient, the electrons drift with higher velocity, or stronger magnetic field is applied.…”
Section: B Condition For Rayleigh Instabilitymentioning
confidence: 80%
“…Therefore, a wider frequency band is observed in a more practical situation. This frequency band is of utmost importance and has not been explored earlier [32][33][34] in the dusty Hall thruster plasma, and hence, this is a novel result.…”
Section: Conditions For Rayleigh Instability: Frequency Bandmentioning
confidence: 99%
“…Moreover, the experimental and theoretical studies indicate that the magnitude of coupling oscillations increase with magnetic flux density, discharge voltage, or coupling intensity coefficient, and this instability has very high wave number values within a frequency ranging from hundreds kilohertz to several megahertz [2]. For a thruster with all other operating parameters (geometry, mass flow rate, static magnetic field and discharge voltage) kept constant, the magnitude of coupling oscillations is mainly decided by the coupling intensity coefficient.…”
Section: Coupling Oscillationsmentioning
confidence: 99%
“…In particular, high-frequency plasma oscillations have recently attracted much attention from the research community [1,2]. In particular, high-frequency plasma oscillations have recently attracted much attention from the research community [1,2].…”
Section: Introductionmentioning
confidence: 99%